Healthy City: Territorial Sustainability Strategies - Pasquotto, Geise Brizotti; Constantino, Norma Regina Truppel (National Journal of City Management, 2026)
Objective – To analyze how the configuration of the urban environment influences the physical, mental, and social health of the population, demonstrating that factors such as green areas, active mobility, environmental comfort, noise control, sociability, safety, and access to essential services constitute structural determinants of well-being. The study seeks to demonstrate that neighborhoods structured under principles of social urbanism and socio-environmental integration have greater potential to promote healthy and sustainable cities.Methodology – The study adopts a qualitative and interdisciplinary approach, based on theoretical and documentary review of institutional reports (PPS, UN, WHO, European Union), national and international scientific studies, Brazilian technical standards (NBR 10.151 and NBR 10.152), and empirical case analyses. The investigation articulates frameworks from public health, urban planning, and sustainability to understand the relationship between the built environment and collective well-being. Based on the bibliographic framework, the study systematizes a set of analytical keys that structure the understanding of the healthy city: i) territorial inequality, ii) environmental comfort, iii) green infrastructure, iv) social capital, v) active mobility, and vi) integrated governance.Originality/Relevance – The study addresses a theoretical gap at the intersection of urban planning, public health, and socio-environmental justice, overcoming fragmented approaches that treat health as an exclusively biological phenomenon. By integrating evidence on socio-spatial segregation, urban heat islands, noise pollution, and social capital, the research reinforces the need for urban policies structured around the social determinants of health, contributing to the contemporary debate on healthy cities in the context of climate change and urban inequalities.Results – The findings indicate that spatial segregation and infrastructural precariousness are associated with poorer health indicators, while thermal differences between neighborhoods disproportionately affect vulnerable populations. Noise pollution negatively impacts well-being, with cognitive and cardiovascular consequences. Conversely, the presence of green spaces, active mobility, and strengthened social support networks reduces risks to physical and mental health. Strategies based on public space qualification and socio-environmental integration demonstrate potential to mitigate environmental impacts and strengthen community bonds.Theoretical/Methodological Contributions – The study advances the debate on healthy cities by integrating environmental health, urban comfort, social capital, and participatory planning within a unified analytical framework. Methodologically, it systematizes diverse empirical evidence from an integrated socio-spatial perspective, offering a framework applicable to public policy formulation and territorial interventions.Social and Environmental Contributions – Socially, the study reinforces the need for urban policies that promote inclusion, belonging, and the reduction of territorial inequalities. Environmentally, it highlights the expansion of green areas, noise control, mitigation of urban heat islands, and the promotion of active mobility as concrete strategies to enhance climate resilience and improve urban quality of life.
Keywords: Healthy City; Sustainability; Urban Planning